The Dynamics of Emotional Behavior and Character Development in Children from Broken Homes: A Case Study at a Juvenile Special Development Institution (LPKA) - Zubaidah Zubaidah; Prio Utomo (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Broken home family conditions often affect children’s emotional development and character formation, particularly among juveniles in conflict with the law who undergo rehabilitation in juvenile correctional institutions. Objective: This study aims to analyse the dynamics of emotional behaviour and the factors influencing character development among juvenile inmates from broken home families at the Class II Juvenile Correctional Institution (LPKA) in Bengkulu City. Method: The study employed a qualitative case study to obtain an in-depth understanding of juveniles' emotional experiences. Data were collected through direct observation, in-depth interviews with five juvenile inmates and two correctional officers, and analysis of relevant documentation. Result: The findings reveal that the juveniles experience complex emotional fluctuations, including sadness, anger, loneliness, and low self-esteem, which are triggered by family conflict, lack of parental attention, and negative social environments. Nevertheless, rehabilitation programs at the LPKA, such as counseling, spiritual activities, educational programs, and social activities, help the juveniles express and manage their emotions more constructively. Conclusion: The study concludes that a holistic, psychosocially supported rehabilitation approach is essential for promoting emotional stability and strengthening character development among juvenile inmates. Contribution: This study enriches the literature on the emotional dynamics of children from broken-home families in institutional rehabilitation contexts.